Emergency Remote Teaching Challenges: The Case of Mexican EFL University Teachers Experiences - Méndez, Héctor; Nuñez, Patricia; Narvaez , Oscar (CIEX JOURNAL, 2022)
The purpose of this study was to record and document experiences and difficulties faced by English teachers during the COVID-19 pandemic, as well as their outcomes and achievements during the implementation of Emergency Remote Teaching (ERT). Delivery of classes through an online environment has been one of the options worldwide to continue with all education programs at all levels in the wake of this current pandemic situation. In this scenario, in most senior high schools and universities in Mexico, online classes have been made mandatory. This case study describes the perceptions and concerns of teachers at these education levels regarding this compulsory transition from face-to-face teaching to ERT. The participants were 7 teachers from different public and private universities in a capital city in the southeast of Mexico. Data was gathered through semi-structured online interviews. Findings suggest that among the key issues that teachers face are technology mishaps, the inadequacy of the materials provided by their institution, privacy issues and institutional slow response to ERT.